Differences in Risk Measurement for Small Unlisted Businesses - Edward A. Vos (Journal of Small Business Finance, 1992)
The use of traditional risk measurement techniques for small unlisted businesses proves difficult due to a lack of market information. A sample of 209 small businesses in New Zealand was gathered to test the possibility of using accounting betas for risk measurement. While the accounting betas calculated for the listed companies in New Zealand did relate similarly to previous studies, several differences with the unlisted businesses are uncovered. The need to develop better measurement devices is highlighted if benchmarks for risk vs. return equilibrium are to be found for the class of small unlisted businesses.
Keywords: L25; G32; 650; Risk; Risk Measurement; Small Business; Unlisted